Evidence Based Medicine : Closer to Patients or Scientists? - Sitaras, Nikolaos M.; Sitaras, Nikolaos M. (IntechOpen, 2012)
Evidence-based medicine (EBM) was introduced to the best benefit of the patient. It has transformed the pathophysiological approach to the outcome approach of today's treatments. Disease-oriented to patient-oriented medicine. And, for some, daily medical practice from patient oriented to case oriented medicine. Evidence has changed the paternalistic way of medical practice. And gave room to patients, who show a tendency towards partnership. Although EBM has introduced a different way of thinking in the day to day medical practice, there is plenty of space for implementation and improvement. This book is meant to provoke the thinker towards the unlimited borders of caring for the patient.
English
Keywords: Birth control, contraception, family planning; Health psychology